Efficient visible light-induced photoelectrocatalytic degradation of rhodamine B by polyaniline-sensitized TiO 2 nanotube arrays - Li, Xin Yong; Teng, W.; Zhao, Q.; Wang, L. (2011)
Self-organized anodic TiO 2 nanotube arrays were sensitized with polyaniline by a simple electrodeposite method. The morphological and structural properties studied by scanning electron microscopy and fourier transform infrared spectroscopy reveal the successful deposition of polyaniline on the nanotube arrays. The polyaniline-sensitized TiO 2 nanotube arrays exhibit a distinguishable red shift on the absorption spectrum. Electrochemical impedance investigation attested to a significant improvement of the interfacial electron-transfer kinetics for promoted electron-hole effective separation. The as-prepared samples showed a high efficiency for the photoelectrocatalytic degradation of rhodamine B under visible-light irradiation (?>400 nm). The enhanced photoelectrocatalytic activity could be attributed to the extended absorption in the visible-light region by the polyaniline and the effective separation of photogenerated carriers driven by the photoinduced potential difference generated at the polyaniline/TiO 2 nanotube arrays interface. © 2011 Springer Science+Business Media B.V.